Managing stress with qigong - Faulkner, Gordon, 1951- (London ; Philadelphia : Singing Dragon, 2011)
Presents a series of stress relief and stress prevention exercises based on the ancient Chinese healing art of qigong that combines physical movement with breathing techniques to promote mind/body harmony.
Includes index.
Keywords: Breathing Exercises; Qi